Features of the organization of Buddhist thinking space - Patsev, Alesiyan (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2015)
The article presents the hypothesis of differences in spatial mode of philosophical thinking. A consequence of these differences arise in the general form of cognitive space. This in turn shapes the interior of the concept and turns it into a miniature model of the general form of cognitive space. Presented are two main forms of epistemological thinking (mental-dimensional schemes). The first is mental-dimensional pyramid scheme in which mental space disappears in a kind of mental peak. In this diagram form the basic concepts of One, the Absolute, God, the substance, the soul as substance and others. The second mental-spatial scheme reminds inverted pyramid. In her mentally absent-gravitational basic concepts (Single, Single Demiurge soul as substance and others.). According to the author this mental-spatial scheme exclusive to the Buddhist philosophical thinking.